Die "Antithesen" der Bergpredigt in neueren Bibelübersetzungen - Röhser, Günter (Theologische Beiträge, 2009)
A comparison of three of the latest German Bible translations of Mt 5:17-48 (Gute Nachricht Bibel, K. Berger / C. Nord, Bibel in gerechter Sprache) shows thnt in all of them the reader is directed towards a certain theological concept. This is achieved through the headlines as well as through individual translations. The headline „Taking the will of God seriously ", which is chosen by GNB, illustrates best that God's manifested will is not simply "interpreted" or ''surpassed" by Jesus, but "fulfilled'', "made perfect''. Therefore a translation like ''And I say unto you " ("Ich nun sage euch'') is better than "But I say unto you", because the former wording expresses the double aspect of Jesus' unique authority as well as the continuity between the former and the eschatological will of God, which Jesus proclaims.